2010
DOI: 10.1108/17511341011030147
|View full text |Cite
|
Sign up to set email alerts
|

Using historic mutinies to understand defiance in modern organizations

Abstract: Purpose: Guided by voice and leadership theory, we articulate the underpinnings of upward defiance (competence deficiency; ignorance of concerns; structural gaps between echelons) and describe the managerial actions that help depose those underpinnings. Design / Methodology / Approach: We analyze 30 historic narrative accounts of actual mutinies. The journalistic accounts from bygone eras provide unparalleled insight into the basic dynamics of mutiny and provide novel insights into organizational defiance. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…Schwartz, in her review of management history research (Schwarz, 2015), concluded that leadership in a crisis was one of the primary themes in recent management history scholarship. This theme has adopted and investigated several areas of leadership, including the (Humphreys et al, 2013) study of the Battle of Blair Mountain to better understand defiance of leaders, as did (Coye et al, 2010) cases of mutinies. Other important studies on leaders and crisis included (Hollow, 2014) examination of bank failures, (Petersen, 2010) study of the Baltimore fire of 1904, (Lopes, 2014) study of the Lisbon earthquake of 1755 focusing on leadership in organizational transformation and (Brady, 2011) study of the battle of Stalingrad and the contrast of rigid vs improvisational approaches to organization.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Schwartz, in her review of management history research (Schwarz, 2015), concluded that leadership in a crisis was one of the primary themes in recent management history scholarship. This theme has adopted and investigated several areas of leadership, including the (Humphreys et al, 2013) study of the Battle of Blair Mountain to better understand defiance of leaders, as did (Coye et al, 2010) cases of mutinies. Other important studies on leaders and crisis included (Hollow, 2014) examination of bank failures, (Petersen, 2010) study of the Baltimore fire of 1904, (Lopes, 2014) study of the Lisbon earthquake of 1755 focusing on leadership in organizational transformation and (Brady, 2011) study of the battle of Stalingrad and the contrast of rigid vs improvisational approaches to organization.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Moreover, it is difficult for temporary teams to change their goals during a project. Humphreys et al (2013) studied narrative accounts from the Battle of Blair Mountain to better understand upward defiance in organizations in addition to offering recommendations with how to deal with an escalation of resistance, Coye et al (2010) analyzed historic mutinies to understand defiance in modern organizations, King (2000) examined Xenophon's retreat in Ancient Greece to address the management of uncertainty, Hollow (2014) investigated the failure of Farrow's Bank in 1920 to understand the role of managerial hubris in the downfall, Petersen (2010) studied the Baltimore fire of 1904, Lopes (2014) utilized the Lisbon earthquake of 1755 to extend our knowledge on the role of leadership in organizational transformation and Brady (2011) analyzed the leading protagonists at the Battle of Stalingrad to examine the merit of improvisation versus rigid command and control in organizations. By examining these historical crises, we can gain insight into group performance under pressure, which can be applied to management techniques used today.…”
Section: Crisis Managementmentioning
confidence: 99%
“…In particular, the authors attend to the extra-role construct voice, defined as "discretionary, upward, and endogenous communication intended to improve an organization despite the risks associated with such communication". Although voice is typically viewed as beneficial, Coye et al (2010) suggest that it can relate to or be used as a means toward upward defiance, thus inhibiting organizational outcomes. The authors further suggest that this type of negative behavior likely stems from employee dissatisfaction, suggesting that the intents or motives behind citizenship behaviors may not always be as expected.…”
Section: Management Lore Example 8: It Is Always Good To Go Above and Beyondmentioning
confidence: 99%